Sistem Keamanan Penerimaan Paket Menggunakan Face Recognition dan Metode Comparison Algorithms dengan Rasberry Pi Berbasis Internet of Things - Frisca Nurul Azmi; Tjut Awaliyah Z; M Iqbal Suriansyah (J-INTECH ( Journal of Information and Technology), 2024)
In this research will use a Raspberry Pi for face processing. Raspberry Pi was chosen because the facial recognition process requires larger CPU processing. Then for input, use a webcam. Then it will be processed by the Raspberry Pi which will then open the door lock and the package can be taken by the buyer. Research Objective "a package receiving sistem using face recognition and comparison algorithms with a Raspberry Pi based on the internet of things" can make it easier for recipients to receive packages safely when the package recipient is not at home. As a result of this research, the author completed several things that became reference points to get maximum results with the most efficient model design possible. This sistem uses a webcam as input which is then processed using a comparison algorithm to compare the registered photos with the frames obtained from the webcam. Then the results will be sent to the website for anyone who tries to open the goods receipt safe to see.